Preparation and characterization of chitosan-hydroxyapatite nanoparticles for gene therapy - Alireza, Lari (2014)
Recently, in pharmaceutical research and industry scientists widely have used polysaccharides and other cationic polymer which is one of the most extensive studies in the field of non-viral DNA carriers for gene delivery and therapy. As a purpose of present study variations of the final solution pH values and filtration were examined for their effects on the particle size and the tendency of particle formation. Chitosan nanoparticles were prepared based on the ionic gelatin of chitosan which hydroxyapatite will adsorb onto the chitosan nanoparticles to form complexes of chitosan and hydroxyapatite. The resulting nanoparticles had a size and positive electrical charge, which vary depending on the formulation conditions. The physicochemical properties of the nanoparticles were determined by scanning electron microscope (SEM). Besides of that, element and chemical characterization of samples were assessed by Energy-dispersive X-ray spectroscopy (EDX). The data revealed that the chitosan/DNA nanoparticles were successfully prepared with a nano size range. Obtained complexes could be loaded by variants of DNA for further use in gene delivery applications.